FAST CHANNEL CONGENITAL MYASTHENIA: REVIEW OF 12 CASES AND TREATMENT CHALLENGES. (29th November 2012) - Finlayson, S; Webster, R; Beeson, D; Jayawant, S; Robb, S; Palace, J
Abstract : The congenital myasthenic syndromes (CMS) are a group of rare inherited disorders causing abnormal neuromuscular junction signal transmission. They result from mutations in genes that encode proteins required for neuromuscular transmission or for the formation and maintenance of the neuromuscular synapse. Fast channel syndrome (FCS) comprises around 5% of genetically confirmed CMS in the UK and is autosomal recessive in inheritance. Here mutations in AChR subunits lead to a kinetic abnormality of the AChR ion channel pore whereby channel opening is abnormally brief (or fast). In the UK the majority of fast channel syndrome present as a severe form of CMS with associated sudden, life-threatening apnoeas on a background of persistent generalised muscle weakness. Patients may have an initial dramatic response to cholinesterase inhibitors but over time this reduces. Addition of 3, 4-Diaminopyridine can be beneficial. We will present 12 cases of FCS detailing underlying mutations and demonstrating the clinical features and discuss management strategies focussing on respiratory issues.